Optimization of digital marketing for MSMEs DASS Sablon, Tempuran - Nuryanto Nuryanto; Alvine Candra; Berno Falalanggi; Faiz Satria Mukti Utama; Alifia Herlin Lutfiannisa; Ikhbal Khasodiq (Universitas Muhammadiyah Magelang, 2022)
One of the most critical factors of a business, which is equally as important as the production unit itself, is marketing. Marketing is the lifeblood of a business to be able to maintain its financial viability. This integrated community service activity (PPMT) aims to assist MSMEs DASS sablon in optimizing the marketing of their products. The method used in this program is socialization and assistance in managing social media as a marketing medium. The result of this program is Instagram social media for promotional media and new t-shirt designs which are marketed using the Pre-order (PO) method for 10 days and obtained 20 buyers. Additionally, videos of partner profiles are produced as supplemental content for digital marketing initiatives.